Pengaruh Investasi, Tenaga Kerja, Pengalaman Kerja dan Kapasitas Produksi Terhadap Nilai Produksi Pengerajin Perak - Ayu Lestari, Dian; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
The purpose of this study to know whether the investment, employment, work experience, and powerful production capacity simultaneously and partially on the value of production silversmith Celuk Village. The results showed variable simultaneous investment, employment, work experience, and production capacity have a positive and significant impact on the value of production silversmith Celuk village, as well as the investment variable, work experience, and the production capacity is partially positive and significant effect, while labor positive and significant impact on the value of production silversmith Celuk Village.
Keywords: Production Value; Invest; Work experience